2013
DOI: 10.1620/tjem.230.233
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Dynamic Balance Is Associated with Falling in Post-Stroke Patients

Abstract: Falling is one of the most common complications of stroke. The purpose of this study was to investigate the impact of falling on cognitive and physical function in post-stroke patients. Further, the predictive factors associated with independence of activity of daily living (ADL) in stroke patients with falls experience were investigated. Sixty-six participants were divided into 2 groups according to history of falling: faller (n = 34) and non-faller (n = 32). All participants were examined for cognitive and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 27 publications
(32 reference statements)
1
21
0
1
Order By: Relevance
“…Chou et al28 found a moderate correlation between the MBI and RMI. Authors reported that a dynamic balance was measured using the RMI in the evaluation of falls.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Chou et al28 found a moderate correlation between the MBI and RMI. Authors reported that a dynamic balance was measured using the RMI in the evaluation of falls.…”
Section: Discussionmentioning
confidence: 96%
“…There was a strong positive correlation between MBI and RMI in our study. In the aforementioned study,28 because of the lack of separate BRS scores it is difficult to discuss the effects of lower extremity BRS values on falls. Pure motor stroke was reported as the most common result of lacunar infarct, but the prognosis was found better than other stroke syndromes 29.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, depression leads to reduced attention and to an increased risk of falling45, 46 ) . Falling is reportedly associated with reduced ADL47, 48 ) . Therefore, the falling risk induced by PSD may be associated with low independence levels in ADL.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Ischemic stroke is a significant cause of gait imbalance and falling, [2,3] with incidence of stroke more than tripling between the 35 and 44 to 65 and 73-year-old age groups. [4,5] Autonomic dysfunction has proven to be both a risk factor and also as a symptom poststroke, attributing to the increased fall risk in stroke survivors.…”
Section: Introductionmentioning
confidence: 99%